Research of the Special Processing Equipment Development and Trial Production of Roller Enveloping End Face Engagement Worm Pair - Kai Wang (Jixie chuandong)
According to the transmission principle and mathematical model of the roller envelope end face meshing worm drive， the conjugate relationship of the roller envelope end face meshing worm is analyzed， and the design scheme of the roller envelope end face meshing worm special processing equipment is proposed， and the special processing equipment is developed and carried out. The worm prototype is trial-produced， and bench test is carried out by using the trial-produced prototype. The results show that the single-stage worm and the worm gear mesh with 5 pairs of teeth， the noise of the end face meshing worm increases with the increase of rotating speed， the noise is between 70 and 93 dB， the transmission efficiency of the end face engagement worm increasing with the load increase and gradually becomes stable， the stable transmission efficiency under different loads is between 40% and 48%. It can provide theoretical basis for the proceeding research of this kind of worm.